2009
DOI: 10.1021/es900556k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mn(II) on the Structure and Reactivity of Biogenic Uraninite

Abstract: The efficacy of a site remediation strategy involving the stimulation of microbial U(VI) reduction hinges in part upon the long-term stability of the product, biogenic uraninite, toward environmental oxidants. Geological sedimentary uraninites (nominal formula UO 2 ) reportedly contain abundant cation impurities that enhance their resistance to oxidation. By analogy, incorporation of common groundwater solutes into biogenic uraninite could also impart stability-enhancing properties. Mn(II) is a common groundwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 23 publications
5
30
1
Order By: Relevance
“…Similarly, biogenic UO 2 was produced via the enzymatic reduction of U(VI) by S. putrefaciens and G. sulfurreducens in the absence of Fe(III) and shows the same salient features as that of nanoparticulate UO 2 produced by biogenic magnetite in this study and reported elsewhere Bargar et al, 2008;Sharp et al, 2009;Veeramani et al, 2009).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Similarly, biogenic UO 2 was produced via the enzymatic reduction of U(VI) by S. putrefaciens and G. sulfurreducens in the absence of Fe(III) and shows the same salient features as that of nanoparticulate UO 2 produced by biogenic magnetite in this study and reported elsewhere Bargar et al, 2008;Sharp et al, 2009;Veeramani et al, 2009).…”
Section: Discussionsupporting
confidence: 85%
“…the number of U atoms bound at the surface of the particle becomes comparable to the number of U atoms within the interior of the particle, resulting in a decrease in the average U-U CN (4.1-6.1), which is consistent with EXAFS in the present study. This under-coordination is consistent with the nanoparticulate size and consequential high proportion of surface-exposed atoms (O'Loughlin et al, 2003;Schofield et al, 2008;Veeramani et al;Sharp et al, 2009). The same EXAFS results were observed for both unpasteurized and pasteurized magnetite samples, confirming that an abiotic process leads to uraninite formation.…”
Section: X-ray Absorption Spectroscopy (Xas)supporting
confidence: 75%
See 1 more Smart Citation
“…The uranium product formed by Shewanella oneidensis MR-1 through bioreduction has previously been identified by means of synchrotron based X-ray powder diffraction (SR-PD), extended X-ray absorption fine structure (EXAFS) spectroscopy, and high-resolution transmission electron microscopy (HR-TEM) Schofield et al 2008;Ulrich et al 2009;Ulrich et al 2008;Veeramani et al 2009). The combined results indicated extracellular nanoparticles of 2-5 nm diameter with a mineral structure and composition homologous to stoichiometric UO 2+x (with x < 0.05) and were consistent with bacteriogenic UO 2 described in other studies, e.g., by Burgos et al (2008) …”
Section: Reaction Product Characterizationmentioning
confidence: 99%
“…As such, it provides justification for geochemical models for bacterial products based on a single set of rate and thermodynamic constants (26,30).…”
Section: Of the Supporting Information)mentioning
confidence: 99%